2021
DOI: 10.3846/btp.2021.13880
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Fintech Continuance Intention of Indonesian Users: The Moderating Effect of Gender

Abstract: This research attempt to analyze risk and benefit factors as well as their influence on sustainability intention of FinTech. We elucidate the Planned Behavior Theory by including the perceived benefits and perceived risk variables to investigate its effect on intention to continue using FinTech. We also examined whether or not men and women are affected differently by the benefits and risk they perceive when using FinTech. Data were collected through online surveys, then being analyzed using GSCA. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…The results were in agreement with similar studies carried out in Malaysia (Lai andLiew, 2021), 10.3389/fpsyg.2022.928735 FIGURE 3 Diagram illustrating the structural model. India (Pal et al, 2021), South Korea (Joo, 2018), and Indonesia (Nurlaily et al, 2021). As for results of the investigation regarding the multi-dimensional perceived value framework, it is noted that the three antecedents can all significantly predict perceived value.…”
Section: Discussionmentioning
confidence: 93%
“…The results were in agreement with similar studies carried out in Malaysia (Lai andLiew, 2021), 10.3389/fpsyg.2022.928735 FIGURE 3 Diagram illustrating the structural model. India (Pal et al, 2021), South Korea (Joo, 2018), and Indonesia (Nurlaily et al, 2021). As for results of the investigation regarding the multi-dimensional perceived value framework, it is noted that the three antecedents can all significantly predict perceived value.…”
Section: Discussionmentioning
confidence: 93%
“…Research has revealed that men generally have a higher usage rate of fintech applications compared to women (Chen et al, 2023). Nonetheless, it means a lot to take note of that distinction in sexual orientation in fintech adoption might shift across various social settings and explicit fintech administrations advertised (Nurlaily et al, 2021). Study has shown that age gender and education do significantly impact the use of Fintech among the farmers (Mathur, 2022).…”
Section: Gender and Educationmentioning
confidence: 99%
“…Sampel peneltian adalah nasabah yang berdomisili di wilayah Jabodetabek. Variabel yang diteliti mengenai hubungan Operational Risk dan Security Risk terhadap Perceived Risk sudah pernah dilakukan secara terpisah, seperti oleh Nurlaily et al, (2021), Sumardi et al, (2022), Keong et al, (2020), Mahardika et al, (2021), Wilson (2021), Sentanu et al (2020), Irawan dan Affan (2020), Liang et al, (2018), Trinh et al,(2020, Marriott and Williams (2018), Jain dan Raman (2022), Ali et al, (2020), Mascarenhas et al (2020), Setyadi et al, (2021).…”
Section: Gambarunclassified
“…Security Risk dapat menyebabkan potensi kerugian karena menyangkut data privasi dari nasabah, seperti kode pin portable nasabah yang dapat diretas oleh beberapa pihak. Semakin tinggi resiko keamanan yang dirasakan nasabah maka intensi nasabah dalam menggunakan Fintech akan menurun oleh sebab itu disimpulkan bahwa Security Risk memiliki hubungan positif dengan Perceived Risk (Nurlaily, Aini, & Asmoro, 2021).…”
Section: Hubungan Security Risk Dan Perceived Riskunclassified